Regularização fundiária como aporte ao desenvolvimento local: reflexões a partir da experiência do município de Ferreira Gomes-AP - LUZ, Milene Miranda (2022)
This study aims to situate the debate about the land regularization policy as a contribution to local development, observing the effects, challenges and possibilities arising from this relationship. The objective of the research is to analyze whether the “Programa Regulariza Ferreira'' is impacting the local development of the municipality of Ferreira Gomes, in the State of Amapá. The research was exploratory and explanatory of a qualitative nature, using bibliographic, documentary and field research. The data were analyzed from the principles of economic, environmental and social sustainability, obtaining as a result that the procedure implemented in the municipality is based only on the legal effects of recognition of the real right to property as it does not comply with the requirements of land regularization as a policy of urban development, not being enough to achieve full development and with practical gains for the local community. Therefore, such a policy must be formulated within the scope of socioeconomic, urban and environmental policies, based on the constitutional principles of democratic management.